2015
DOI: 10.1155/2015/898202
|View full text |Cite
|
Sign up to set email alerts
|

The Anticandidal and Toxicity Properties of Lampranthus francisci

Abstract: Fungal infections have been rising due to the increasing number of immunocompromised patients and intensive use of some antifungal agents. Lampranthus francisci is an ornamental succulent plant. In Zimbabwe, the fresh sap from the leaves is used to treat fungal scalp infections. The activity of L. francisci fresh and dry acetone, ethanol, hydroethanolic, and aqueous extracts against Candida albicans and Candida krusei was determined. Mouse peritoneal cavity cells and sheep red blood cells were used to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…e ethanol:water extract was the most potent against all 4 test strains. High potency of the hydroethanolic extracts has been reported elsewhere against Candida [30] and bacteria [31]. Maximal activity of the ethanol:water extract was observed against S. epidermidis with total inhibition at 100 μg/mL of the extract.…”
Section: Discussionsupporting
confidence: 52%
“…e ethanol:water extract was the most potent against all 4 test strains. High potency of the hydroethanolic extracts has been reported elsewhere against Candida [30] and bacteria [31]. Maximal activity of the ethanol:water extract was observed against S. epidermidis with total inhibition at 100 μg/mL of the extract.…”
Section: Discussionsupporting
confidence: 52%
“…It has been also reported that genus Mesembryanthemum has long been used as food and in traditional medicine for the treatment of liver diseases and diabetes . The species Lampranthus francisci showed strong anticandidal activity . Moreover, studies showed that Lampranthus spectabilis has high phenolic content and displays strong antioxidant activity .…”
Section: Introductionmentioning
confidence: 97%
“…L. francisci is an ornamental succulent plant. The hydro-alcohol extracts of L. francisci caused hemolysis of sheep cells and had a fungicidal activity (Moyo and Mukanganyama, 2015).…”
Section: Introductionmentioning
confidence: 99%